1982
DOI: 10.1366/0003702824639303
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carlin-Type Gold Ore by Photoacoustic, Raman, and EPR Spectroscopy

Abstract: Low-grade carbonaceous gold ore (0.01 to 1.8 oz/ton of gold) from the Carlin mine in Elko county, Nevada, has been characterized by a variety of analytical and spectroscopic techniques with emphasis on vibrational spectroscopy. A particular concern was determining the nature of the carbon-containing material in the ore. It was found that in addition to the anticipated carbonate, finely disseminated elemental carbon is present in amounts ranging from 0.062 to 0.43 wt. %. Contrary to previous reports, no detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…Friedman et al (1982) made similar hypotheses related to Russian disseminated gold deposits. Nelson et al (1982) extracted 50g of Carlin carbonaceous ore for 96 hours and reported obtaining only sulfur with no detectable HCS, in contrast to the results of Radtke and Scheiner (1970) and of this study. Our Soxhlet-extraction technique involves using a polished copper strip in the solvent-boiling pot to remove elemental sulfur (a standard procedure).…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Friedman et al (1982) made similar hypotheses related to Russian disseminated gold deposits. Nelson et al (1982) extracted 50g of Carlin carbonaceous ore for 96 hours and reported obtaining only sulfur with no detectable HCS, in contrast to the results of Radtke and Scheiner (1970) and of this study. Our Soxhlet-extraction technique involves using a polished copper strip in the solvent-boiling pot to remove elemental sulfur (a standard procedure).…”
Section: Introductioncontrasting
confidence: 99%
“…Thus, the lack of, or light, color of extracts from Carlin-type rocks predisposes one to assuming no bitumen exists in the extracts. also reported that no bitumen was recovered from solvent extraction of rocks, similar to those studied by Nelson et al (1982), but from Jerritt Canyon, thus seemingly confirming Nelson et al (1982) and negating Radtke and Scheiner (1970). Moreover, other analyses carried out by were interpreted as demonstrating that the carbon in their rocks was "burned-out" (overmature) and incapable of either generating, or being associated with, HCS.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations